1997
DOI: 10.1002/(sici)1097-0142(19971001)80:7<1234::aid-cncr6>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Surgical pathologic factors that predict recurrence in stage IB and IIA cervical carcinoma patients with negative pelvic lymph nodes

Abstract: with pelvic lymph node dissection. The study group was composed of 196 lymph node negative patients. Pathology slides were reviewed and multivariate analysis 1 Department of Obstetrics and Gynecology, Acperformed to identify independent prognostic factors. ademic Medical Center, University of Amsterdam, Amsterdam, The Netherlands. RESULTS.The recurrence rate in the study group was 7.7%. In multivariate analysis, the following factors were identified as independent risk factors for recurrence: 2 Department of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 1 publication
1
33
2
Order By: Relevance
“…[22][23][24] Others have found results that are the opposite of what is present above. 25 Studying prognostic factors in 196 cases of carcinoma of the uterine cervix in stages IB and IIA without metastases in the lymph nodes, Samlal et al found that the risk of recurrence was around 2.5 times greater in cases with severe infl ammatory reaction in the uterine cervix. 25 Lack of standardization of the criteria utilized for defi ning the intensity of the infl ammatory reaction is probably responsible for this difference in results.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…[22][23][24] Others have found results that are the opposite of what is present above. 25 Studying prognostic factors in 196 cases of carcinoma of the uterine cervix in stages IB and IIA without metastases in the lymph nodes, Samlal et al found that the risk of recurrence was around 2.5 times greater in cases with severe infl ammatory reaction in the uterine cervix. 25 Lack of standardization of the criteria utilized for defi ning the intensity of the infl ammatory reaction is probably responsible for this difference in results.…”
Section: Discussioncontrasting
confidence: 89%
“…25 Studying prognostic factors in 196 cases of carcinoma of the uterine cervix in stages IB and IIA without metastases in the lymph nodes, Samlal et al found that the risk of recurrence was around 2.5 times greater in cases with severe infl ammatory reaction in the uterine cervix. 25 Lack of standardization of the criteria utilized for defi ning the intensity of the infl ammatory reaction is probably responsible for this difference in results. In the present study, the fact that a single pathologist reviewed the tumor slides reduced the bias produced by variation between observers.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with AdCa after RH is unclear, primarily because studies have been performed on small numbers of patients. Some of these studies found that patients with AdCa have poorer prognosis than do those with SCCa (Hopkins and Morley, 1991;Eifel et al, 1995;Look et al, 1996;Samlal et al, 1997;Lai et al, 1999;Kim et al, 2000;Nakanishi et al, 2000), whereas other reports found no differences in prognosis (AntonCulver et al, 1992;Miller et al, 1993;Shingleton et al, 1995;Grisaru et al, 2001;Ayhan et al, 2004;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009). Therefore, the prognosis after RH and the optimal management of AdCa are still a subject of debate.…”
mentioning
confidence: 99%
“…Advanced International Federation of Gynecology and Obstetrics (FIGO) stage, larger tumor size, and presence of lymph node metastasis have been reported as negative prognostic factors for patients with cervical cancer who are treated with concurrent chemoradiotherapy (CCRT) [2,3]. Pelvic and/or paraaortic lymph node status is a strong independent prognostic factor in cervical cancer [4,5]. Lymph node metastases in cervical cancer have the propensity to progress in an orderly fashion from the pelvis to the abdomen, the supraclavicular region, and then to the mediastinum.…”
Section: Introductionmentioning
confidence: 99%